Type XXVIII Collagen Regulates Renal Interstitial Fibrosis and Epithelial-Mesenchymal Transition by SREBP1-Mediated HKDC1 Expression - Li, Linlin; Zou, Qi; Li, Binbin; Huang, Lushi; Wei, Lixin (Journal of the Renin-Angiotensin-Aldosterone System, 2022)
Background. A novel collagen called type XXVIII collagen (COL28) is involved in cancer and lung fibrosis. Preliminary data showed that renal tubular epithelial cells could proliferate, migrate, and undergo an epithelial-mesenchymal transition (EMT) when COL28 was overexpressed; however, it is still unknown how this occurs and what the underlying mechanism is. Methods. We analyzed the differential expression of genes (DEGs) in the stable COL28 overexpression HK-2 cell lines by RNA-sequencing analysis, before which Gene Ontology (GO) and Kyoto Encyclopedia of Gene and Genomes (KEGG) analyses were performed. Genes related to COL28 promoting HK-2 cell proliferation and EMT were screened and verified. By using western blot and immunofluorescence, the effects of COL28 on the expression of α-SMA, E-cadherin, Snail, HKDC1, and SREBP1 were detected. The effect of COL28 overexpression on renal fibrosis in unilateral ureteral obstruction (UUO) mice was detected by H&E and Masson staining. HKDC1 interference agent was synthesized and transfected into the HK-2 cell line stably overexpressing COL28. In HK-2 cells, the effects of HKDC1 interference on the expression of α-SMA, E-cadherin, and Snail were detected. Results. We screened and verified that HKDC1 was related to COL28 and promoted HK-2 cell proliferation and EMT. WB showed that in HK-2 cells, COL28 overexpression increased α-SMA, Snail, HKDC1, and SREBP1 expressions and decreased E-cadherin expression. Overexpression of COL28 aggravated renal interstitial fibrosis in UUO mice; upregulated α-SMA, Snail, HKDC1, and SREBP1 expressions; and decreased the E-cadherin protein expression in UUO mice. Interference of HKDC1 expression promoted the E-cadherin protein expression while inhibiting α-SMA, Snail, HKDC1, and SREBP1 protein expressions. Conclusion. Overexpression of COL28 can aggravate renal interstitial fibrosis by encouraging renal tubular epithelial cells to undergo EMT, and interference with HKDC1 expression can alleviate fibrosis by reversing EMT induced by COL28 overexpression.